The fall of the genome protectors triad: PBRM1, SETD2, and BAP1’s impact on metabolism and immunity in clear cell renal cell carcinoma - Johnson, Mathieu; Turcotte, Sandra (Frontiers in Cell and Developmental Biology, 2026)
The loss of chromosome 3p and the inactivation of the tumor suppressor gene von Hippel-Lindau (VHL) were identified in clear cell renal cell carcinomas (ccRCC) over three decades ago. Since then, mutations in genes for the three chromatin modulators, polybromo 1 (PBRM1), SET domain-containing 2 (SETD2), and BRCA1-associated protein-1 (BAP1), have been recognized as common in ccRCC. Although these genomic alterations are central to understanding ccRCC’s development, other deregulated cellular processes are also prominent in these tumors. Metabolic reprogramming is a key hallmark of this disease, characterized by various changes linked to the stabilization of hypoxia-inducible factors (HIF), including increased aerobic glycolysis, elevated lipid levels, and glutamine dependence for cell survival. Additionally, HIF-α stabilization plays a crucial role in regulating the immune system, thereby enhancing CD8+ T lymphocyte cytotoxicity. Immune checkpoint inhibitors (ICI) are now used as first-line treatments to target the often highly infiltrated tumor microenvironment of ccRCC. However, the effectiveness of ICI varies and is difficult to predict. Although emerging studies are beginning to provide insight, evidence suggests roles for PBRM1, SETD2, and BAP1 in metabolic regulation and in shaping the tumor immune microenvironment in ccRCC. Here, we review recent advances in this field and examine their impact on the management of ccRCC.